Diagnostic and prognostic significance of systemic alkyl quinolones for P. aeruginosa in cystic fibrosis: a longitudinal study - Barr, Helen L.; Halliday, Nigel; Barrett, David A.; Williams, Paul; Forrester, Doug L.; Peckham, Daniel; Williams, Kate; Smyth, Alan R.; Honeybourne, David; Whitehouse, Joanna L.; Nash, Edward F.; Dewar, Jane; et al. (Elsevier, 2017)
Background Pulmonary P. aeruginosa infection is associated with poor outcomes in cystic fibrosis (CF) and early diagnosis is challenging, particularly in those who are unable to expectorate sputum. Specific P. aeruginosa 2-alkyl-4-quinolones are detectable in the sputum, plasma and urine of adults with CF, suggesting that they have potential as biomarkers for P. aeruginosa infection. Aim To investigate systemic 2-alkyl-4-quinolones as potential biomarkers for pulmonary P. aeruginosa infection. Methods A multicentre observational study of 176 adults and 68 children with CF. Cross-sectionally, comparisons were made between current P. aeruginosa infection using six 2-alkyl-4-quinolones detected in sputum, plasma and urine against hospital microbiological culture results. All participants without P. aeruginosa infection at baseline were followed up for one year to determine if 2-alkyl-4-quinolones were early biomarkers of pulmonary P. aeruginosa infection. Results Cross-sectional analysis: the most promising biomarker with the greatest diagnostic accuracy was 2-heptyl-4-hydroxyquinoline (HHQ). In adults, areas under the ROC curves (95% confidence intervals) for HHQ analyses were 0.82 (0.75–0.89) in sputum, 0.76 (0.69–0.82) in plasma and 0.82 (0.77–0.88) in urine. In children, the corresponding values for HHQ analyses were 0.88 (0.77–0.99) in plasma and 0.83 (0.68–0.97) in urine. Longitudinal analysis: Ten adults and six children had a new positive respiratory culture for P. aeruginosa in follow-up. A positive plasma HHQ test at baseline was significantly associated with a new positive culture for P. aeruginosa in both adults and children in follow-up (odds ratio (OR) = 6.67;-95% CI:-1.48–30.1;-p = 0.01 and OR = 70; 95% CI: 5–956;-p < 0.001 respectively). Conclusions AQs measured in sputum, plasma and urine may be used to diagnose current infection with P. aeruginosa in adults and children with CF. These preliminary data show that plasma HHQ may have potential as an early biomarker of pulmonary P. aeruginosa. Further studies are necessary to evaluate if HHQ could be used in clinical practice to aid early diagnosis of P. aeruginosa infection in the future.